Distinct cholecystokinin receptors in brain and pancreas. - Innis, R B (1980)
125I-Labeled (Bolton-Hunter) cholecystokinin triacontatriapeptide (CCK-33) binds saturably and reversibly to distinct receptors in brain and pancreatic membranes. The peptide specificity of pancreatic CCK binding is the same as that for pancreatic amylase release. In brain, gastrin and pentagastrin display nanomolar affinity for binding sites, whereas in pancreas these two peptides are virtually inactive. Though these differences indicate that brain and pancreas possess distinct CCK receptors, the two tissues show some similarities. Both pancreas and brain receptors show greater sensitivity to sulfated than to desulfated COOH-terminal octapeptide of CCK and display dissociation constants of 0.3-9.5 nM. The pancreas possesses about 300 times more binding sites than does brain. CCK binding in both brain and pancreas is enhanced by divalent cations and reduced by monovalent cations. Receptor binding in both tissues is regulated in a selective fashion by guanyl nucleotides.